Pengaruh Kecepatan Inovasi dan Digital Marketing terhadap Daya Saing pada Wirausaha Penjahit Perempuan Berbasis UMKM Home Industry di Kota Makassar - Nurjaya, Nurjaya; Asmawiyah Asmawiyah; Megawhati Artiyani (Al-Buhuts, 2024)
This research aims to examine the effect of: (1) speed of innovation on competitiveness, (2) digital marketing on competitiveness, (3) speed of innovation on digital marketing, (4) speed of innovation on competitiveness through digital marketing. The analysis method used is path analysis using Partial Least Square (PLS). The object of this research is female tailor entrepreneurs in the MSME home industry in Makassar City, totaling 133 entrepreneurs. The research results show that: (1) speed of innovation has a positive but not significant effect on competitiveness, (2) digital marketing has a positive and significant effect on competitiveness, (3) speed of innovation has a positive and significant effect on digital marketing, (4) speed of innovation has a positive and significant effect on competitiveness through digital marketing.